A new three-phase low THD power supply with high-frequency isolation and 60V/200A regulated DC output - De Seixas, F. J M [UNESP] (2001)
This work proposes a new isolated high power factor 12kW power supply based on an 18-pulse transformer arrangement. Three full-bridge converters are used for isolation and to balance the DC-link currents, without current sensing or a current controller. The topology provides a regulated DC output with a very simple control strategy. Simulation and experimental results are presented in this paper.